Describing The Nutritional Outcomes Following Paediatric Liver Transplantation At A Tertiary Hospital In South Africa - Ndhlovu, Lesego (Department of Paediatrics and Child Health, 2024)
Background: Nutrition in chronic liver disease is an important marker of post- liver transplant outcomes in children and is monitored judiciously pre-transplantation. There is a paucity of data on post-transplant nutritional outcomes, particularly in the developing world setting. Aim: To describe the nutritional outcomes of children following liver transplantation. Methods: A retrospective study of patient's receiving post-transplant care at Red Cross War Memorial Children's Hospital in Cape Town, South Africa from 2004 – 2019. Results: 31 children were included in the analysis. Pre-transplant prevalence of stunting was 57,1%, with 32,1% of children severely stunted. At 24 months post-transplant 65,5% of children were stunted, with 44,8% severely stunted. Overweight and obesity prevalence was 0% pretransplant, and 32,2% and 27,6% at 12- and 24-months post-transplant respectively. Biliary atresia was the diagnosis in 89,5% of children with stunting at 24 months vs in 50% of children without stunting at 24 months post-transplant (p = 0.03). Mean pre-transplant albumin was lower in children with stunting at 24 months post-transplant than in children without stunting (26,7 vs 29,6 g/L respectively; p < 0,001). Age at transplant was lower in children with stunting at 24 months post-transplant vs children without stunting (40,7 versus 91,5 months; p < 0.001). Twenty-one (67,7%) children developed hypertension post-transplant. Conclusion: Stunting, hypertension and overweight/obesity are highly prevalent post paediatric liver transplantation. Lower pre-transplant albumin, younger age at transplant, and diagnosis of biliary atresia were associated with post-transplant stunting. Post-transplant growth monitoring seems prudent to prevent the development of overnutrition and associated metabolic complications.